2015
DOI: 10.1111/mec.13238
|View full text |Cite
|
Sign up to set email alerts
|

Not all are free‐living: high‐throughput DNA metabarcoding reveals a diverse community of protists parasitizing soil metazoa

Abstract: Protists, the most diverse eukaryotes, are largely considered to be free-living bacterivores, but vast numbers of taxa are known to parasitize plants or animals. High-throughput sequencing (HTS) approaches now commonly replace cultivation-based approaches in studying soil protists, but insights into common biases associated with this method are limited to aquatic taxa and samples. We created a mock community of common free-living soil protists (amoebae, flagellates, ciliates), extracted DNA and amplified it in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 108 publications
3
75
0
Order By: Relevance
“…A total of 20 sessile and 13 protist taxa were likely present on the legs of spider crabs and other arthropods. In fact, epiphytes, endosymbionts and also parasites are commonly described in sequence libraries (Geisen et al, 2015; de Vargas et al, 2015). Motile OTUs (e.g., among arthropods, molluscs and echinoderms) may be part of the diet of carnivorous annelids and thus present in the section of their digestive tract that was used for DNA extraction.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 20 sessile and 13 protist taxa were likely present on the legs of spider crabs and other arthropods. In fact, epiphytes, endosymbionts and also parasites are commonly described in sequence libraries (Geisen et al, 2015; de Vargas et al, 2015). Motile OTUs (e.g., among arthropods, molluscs and echinoderms) may be part of the diet of carnivorous annelids and thus present in the section of their digestive tract that was used for DNA extraction.…”
Section: Discussionmentioning
confidence: 99%
“…This method is known as eDNA metabarcoding . eDNA metabarcoding has been used in many studies including detection of fish species (Thomsen et al, 2012a,b;Kelly et al, 2014;Evans et al, 2016), aquatic plants (Cowart et al, 2015;Visco et al, 2015), macroinvertebrates (Elbrecht and Leese, 2015), amphibians (Evans et al, 2016), arthropods (Yu et al, 2012), protists (Pawlowski et al, 2014;Geisen et al, 2015;Kosakyan et al, 2015), soil biodiversity (Bienert et al, 2012;Taberlet et al, 2012;Yoccoz et al, 2012), diet assessment (Valentini et al, 2009;Deagle et al, 2013;De Barba et al, 2014) and ballast water surveillance (Zaiko et al, 2015). This study presents the first eDNA metabarcoding results of an entire lake ichthyofauna.…”
Section: Discussionmentioning
confidence: 91%
“…Though there are concerns about how well read/sequence frequency reflects the relative abundance of populations in an environmental sample-driven largely by differential amplification success of target genomes [3,[7][8][9]12,13], it is worth noting that at least two recent studies-one on nematodes and one on marine fouling communities-found a strong correlation between the proportion of metabarcoding reads from a taxon and the relative abundance of that taxon given point counts [31,39], as well as a strong correlation with taxon frequency from individual barcode data. If this relationship is supported in further studies, and if we can use information such as the number of haplotypes in a taxon as complementary information for minimum abundance, then we may start to improve on our ability to recover actual ecology from actual molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing (NGS) has permitted the now-commonplace exploration of fungal, bacterial, and viral diversity by generating 10 5 -10 7 sequence reads per sample and using barcoding approaches (match of sequence to known taxonomic samples for that genomic region) to identify the lineages, OTUs, or species present and their relative abundance. While there is no doubt that this has transformed our understanding of functional ecosystem processes and ecology of microbes, other prokaryotes, and microscopic eukaryotes at this scale [3][4][5][6][7], there are definite limitations-including the difficulty of reliably matching molecular sequence data to described species or taxonomic diversity [8,9]. For example, some taxa (e.g.…”
Section: Introductionmentioning
confidence: 99%